2011
DOI: 10.1016/j.meegid.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species spread of SCCmec IV subtypes in staphylococci

Abstract: Staphylococcal chromosomal cassette mec (SCCmec) is a mobile genetic element that carries resistance genes for beta-lactam antibiotics. Coagulase-negative staphylococci, such as S. epidermidis, are thought to be a reservoir of diverse SCCmec elements that can spread to the most virulent staphylococcal species, S. aureus, but very little is known about the extent of crossspecies spread of these elements in natural populations or their dynamics in different species. We addressed these questions by using a sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 66 publications
1
35
0
Order By: Relevance
“…SCCmec type IV is the most common type found in MRSA worldwide. This type is also the most variable with eight subtypes, which is probably a result of its higher mobility compared to the other SCCmec types [83][84]. The most recently described SCCmec elements, type IX, X and XI have all been found in MRSA strains considered to be of animal origin, and carry at least one operon encoding resistance to heavy metals, which appears to be an attribute of SCCmec elements originating in animals [58].…”
Section: Sccmecmentioning
confidence: 97%
“…SCCmec type IV is the most common type found in MRSA worldwide. This type is also the most variable with eight subtypes, which is probably a result of its higher mobility compared to the other SCCmec types [83][84]. The most recently described SCCmec elements, type IX, X and XI have all been found in MRSA strains considered to be of animal origin, and carry at least one operon encoding resistance to heavy metals, which appears to be an attribute of SCCmec elements originating in animals [58].…”
Section: Sccmecmentioning
confidence: 97%
“…insertion sequences, transposons and plasmids, which are located in the joining regions (IWG, 2009). The occurrence of a very similar SCCmec cassette in different species provided evidence that genetic trans fer of this element occurs between species in nature (Barbier et al, 2010;Hanssen and Ericson Sollid, 2006;Smyth et al, 2010). Moreover, Bloemendaal et al (2010) demonstrated in vitro the transfer of SCCmec IV from S. epidermidis to the most virulent staphylococcal spe cies, Staphylococcus aureus.…”
mentioning
confidence: 99%
“…Albatineh et al (1) had previously discussed the correction for chance agreement for several similarity indices, including W. Although this correction was never applied in the context of microbial typing studies, others have previously acknowledged the importance and usefulness of such a correction (15).…”
mentioning
confidence: 99%